2022
DOI: 10.1007/s43683-022-00082-3
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Test Anxiety Using Game-Based Assessment

Abstract: This paper identifies an opportunity to integrate gamification in undergraduate biomedical engineering (BME) classrooms to alleviate student test anxiety and promote student perception of their academic performance. Gamification is a popular educational strategy that does not appear to be widely explored or adopted in higher education, particularly in a BME setting. This study proposes methods for the development, implementation, and evaluation of academic games and provides concrete practices and detailed ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
0
1
Order By: Relevance
“…Similar to the results of Year 1, a group-wise comparison of each category of students in Year 2 revealed that mean anxiety scores after assessments with gamification were similar to the mean anxiety scores after assessments without gamification. This is in contrast to several studies stating that gamification decreases test anxiety 15 . A previous study established the association of gamification with an increase in motivation and a subsequent decrease in test anxiety 5 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to the results of Year 1, a group-wise comparison of each category of students in Year 2 revealed that mean anxiety scores after assessments with gamification were similar to the mean anxiety scores after assessments without gamification. This is in contrast to several studies stating that gamification decreases test anxiety 15 . A previous study established the association of gamification with an increase in motivation and a subsequent decrease in test anxiety 5 .…”
Section: Discussioncontrasting
confidence: 99%
“…But now that I study I feel more competent. 'In agreement with the existing data, the healthy competition generated by the leaderboard was also viewed as a source of motivation by the students 15 . 'So that I could maintain my rank and yeah that was something that was good and Yes, indeed it was a healthy competition.'…”
Section: Discussionsupporting
confidence: 85%